Research trends in the mental health and multimorbidity of older people from 2002 to 2022: A bibliometric analysis via CiteSpace - Zhou, Jie; Song, Dan; Ma, Juanjuan; Zhang, Guowen; Wu, Chuduo; Chen, Qian; Zeng, Li (Frontiers in Psychiatry, 2023)
Purpose: Using bibliometric analysis, the objective of this study was to identify research hotspots and trends on multimorbidity and mental health in older adults. This could help guide future research on this topic. Methods: We searched the Web of Science Core Collection for eligible studies. Type of publications were not restricted and the timeframe was set between 2002 and 2022. Knowledge maps were created using CiteSpace to visualize publications, nations, journals, institutions, authors, cited references, and keywords. Microsoft Excel displayed pertinent tables. Results: A total of 216 studies were collected for analysis. The annual publication over the past twenty years demonstrated an upward trend. The main contributors in publications were in North America, Europe, Asia, and Oceania, of which aging was a primary issue. However, collaboration between countries, institutions, and authors were relatively sparce. Cluster analysis and co-citation analysis of references and keywords revealed that the research field could be subdivided into four themes: social psychology as the fundamental disciplinary base, Prevalence of mental disorders and multimorbidity in older adults, pertinent health conditions, and effective interventions. Research trends at present lies in health status, risk factors of prognoses, and effective interventions for prevention and management. Conclusion: The results revealed a reciprocal risk relationship between mental health and multimorbidity. Mental disorders such as depression and anxiety in older adults with multimorbidity garnered considerable interest in the defined population, and further exploration is still promising. Substantial studies on evidence-based prevention and treatment strategies are warranted for improved prognoses.